Sistem Informasi Geografis Diare Pada Balita Di Wilayah Kerja Puskesmas Banjarbaru - Noraida Noraida; Abdul Khair; Munawar Raharja (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2014)
Abstract: Geographic Information System of Diarrhea in Children in the Area of Puskemas Kota Banjarbaru. Incidence of diarrhea was always found every year in Banjarbaru. Incidence rate of diarrhea in Banjarbaru in 2009 to 2012 are respectively 20.98, 19.86, and 16.39. The presentation of data on the incidence of diarrhea mainly done using tables and graphs. The aim of the study was to describe the incidence of diarrhea in children aged less than 5 years in the area of Puskemas Kota Banjarbaru using geographic information system. This research is a descriptive study. Four of the eight health centers in Banjarbaru was chosen as samples. All children aged less than 5 years old who suffered from diarrhea in the four regions had been recorded. Furthermore, measurements of the coordinates of the house where there is a child aged less than 5 years of the living was done. Based on data from the coordinates, thematic maps of the incidence of diarrhea was made. The results showed that during the months of January to June 2013, the incidence of diarrhea is solid in the areas of Puskesmas Banjarbaru and Puskesmas Sungai Besar, is width in the Puskesmas Sungai Ulin, and is solid and long in the area of Puskesmas Cempaka. The results showed that during the months of January to June 2013, the incidence of diarrhea is solid in the areas of Puskesmas Banjarbaru and Puskesmas Sungai Besar, is width in the Puskesmas Sungai Ulin, and is solid and long in the area of Puskesmas Cempaka. It is recommended that a follow-up is done in order to prevent or reduce the incidence of diarrhea through concrete and effective interventions.Keywords  :   Diarrhea; GIS; Banjarbaru